A preliminary microbial study of used O.P. burs - Apolinario, Melissa A.
54 regular senior clinicians from the U.P. College of Dentistry were given questionnaires regarding the reuse of dental burs and certain clinical practices in cleaning burs. 18 senior clinicians from the Aug 26 - Sept. 27 1991 O.P. shift participated in the experimental part of the study using sterile no. 700 carbide fissure burs in preparing incipient class II cavity preparations during their practical examination. These burs were then subjected to microbiological testing. The results turned out to be that: The current clinical practices regarding the reuse of dental burs could pose as a health threat due to the lack of aseptic techniques. The microbial content of such used burs included potentially pathogenic Gram-positive bacteria (Staphylococcus and Streptococcus species) and Gram-negative bacteria Neisseria catarrhalis). This further points to the need for aseptic clinical techniques due to the presence of such bacteria which could cause infection or disease through cross-contamination.